International handbook of research on children's literacy, learning and culture - Hall, Kathy, 1952- (Chichester, West Sussex : Wiley-Blackwell, 2013)
"The International Handbook of Research in Children's Literacy, Learning and Culture presents a careful distillation of the current research in the field of primary years literacy studies"--
Part I. Society, Culture, and Community: 1. Literacies in homes and communities / Kate Pahl and Cathy Burnett; 2. Critical multimodal literacies: synergistic options and opportunities / Margaret Mackey and Margaret Shane; 3. Books, toys, and tablets: playing and learning the age of digital media / Helen Nixon and Erica Hateley; 4. LIteracy education in the age of new media / Bill Green and Catherine Beavis; 5. Connecting with parents and the community in an urban primary school: creative partnerships to build literacy/ies / Pat Thomson and Johanne Clifton; 6. At home and at school: bridging literacy for children from poor rural or marginalized urban communities / Celia R. Rosemberg, Alejandra Stein, and Florencia Alam; 7. Temporality, trajectory, and early literacy learning / Catherine Compton-Lilly; 8. 'This is a job for Hazmat Guy!': global media cultures and children's everyday lives / Victoria Carrington and Clare Dowdall; 9. Literacy as shared consciousness: a neurocultural analysis / Alicia Curtin and Kathy Hall; 10. An ethnographic long look: language and literacy over time and space in Alaska native communities / Perry Gilmore and Leisy Wyman; 11. Understanding English language learners' literacy from a cultural lens: an Asian perspective / Guofang Li; 12. Exploring multiple literacies from homes and communities: a cross-cultural comparative analysis / Iliana Reyes and Moisés Esteban-Guitart; 13. Funds of knowledge in changing communities / Luis C. Moll, Sandra L. Soto-Santiago, and Lisa Schwartz; 14. The hand of play in literacy learning / Shirley Brice Heath -- Part II. School, Culture, and Pedagogy: 15. Building word and world knowledge in the early years / Susan B. Neuman, Ashley M. Pinkham, and Tanya Kaefer; 16. The unfulfilled pedagogical promise of the dialogic in writing: intertextual writing instruction for diverse settings / Rebecca Jesson, Judy Parr, and Stuart McNaughton; 17. Reading engagement research: issues and challenges / Sue Ellis and Cassandra S. Coddington; 18. Opening the classroom door to children's literature: a review of research / Evelyn Arizpe, Maureen Farrell, and Julie McAdam; 19. Writing in childhood cultures / Anne Haas Dyson and Sophie Dewayani; 20. Children's and teachers' creativity in and through language / Teresa Cremin and Janet Maybin; 21. Educational dialogues / Karen Littleton and Neil Mercer; 22. Literacy and curriculum: language and knowledge in the classroom / Peter Freebody, Eveline Chan, and Georgina Barton; 23. The digital challenge / Sandra Schamroth Abrams and Guy Merchant; 24. Digital literacies in the primary classroom / Rachael Levy, Dylan Yamada-Rice, and Jackie Marsh; 25. Developing online reading comprehension: changes, challenges, and consequences / Bernadette Dwyer; 26. Hybrid literacies in a post-hybrid world: making a case for navigating / Elizabeth Birr Moje; 27. Official literacy practices co-construct racialized bodies: three key ideas to further integrate cultural and 'racially literate' research / Karl Kitching; 28. Emotional investments and cries of truth: gender, class, and literacies / Stephanie Jones and Kristy Shackelford; 29. What does human geography have to do with classrooms? / Margaret Sheehy; 30. Space, place, and power: the spatial turn in literacy research / Kathy A. Mills and Barbara Comber -- Part III. Teachers, Culture, and Identity: 31. On becoming teachers: knowing and believing / Jennifer I. Hathaway and Victoria J. Risko; 32. Reforming how we prepare teachers to teach literacy: Why? What? How? / Brian Cambourne and Julie Kiggins; 33. Teachers' literate identities / Toni Gennrich and Hilary Janks; 34. Constructing a collective identity: professional development for twenty-first century pedagogy / Catherine M. Weber and Taffy E. Raphael; 35. Raising literacy achievement levels through collaborative professional development / Eithne Kennedy and Gerry Shiel; 36. Teacher research on literacy: turning around to students and technology / Christopher S. Walsh and Barbara Kamler.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Language arts (Primary) -- Handbooks, manuals, etc; Reading (Primary) -- Handbooks, manuals, etc; Literacy -- Handbooks, manuals, etc; Multicultural education; EDUCATION -- Teaching Methods & Materials -- Reading & Phonics; EDUCATION -- Teaching Methods & Materials -- Reading & Phonics; Language arts (Primary); Literacy; Multicultural education; Reading (Primary); Electronic books; Handbooks and manuals